Lightning environment in Burundi - Nibigira, Edward; Gomes, Chandima (2014)
This paper presents preliminary studies on the lightning accident details in Burundi, a landlocked country in East Africa. The reported lightning incident record in 2012 and 2013 depicts that there are 52 human deaths, 94 human survivals with injuries and 40 deaths of livestock. Makamba province recorded the highest human casualties with 14 deaths and 69 injuries whereas Nyanza-Lac commune of the same province topped the list with 8 deaths and 52 injuries. The statistics do not justify the 1:10 ratio of death : injury as it is reported in USA. The statistics may be a gross underestimation as many lightning accidents are not reported due to lack of communication, especially in the rural areas. Gomes-Kadir equation estimates the death rate as 52 per year, a figure twice as high as that was observed in this study. The analysis of information for incidents over few more years reveals that seeking shelter under ungrounded metal-roofed buildings is extremely dangerous as multiple deaths may occur in the event of a lightning strike to the roof.